Hydrothermally Synthesized Hydroxyapatite-Silica Composites with Enhanced Mechanical Properties for Bone Graft Applications - Atiek Rostika Noviyanti; Juliandri Juliandri; Engela Evy Ernawati; Haryono Haryono; Solihudin Solihudin; Dina Dwiyanti; Azman Ma’amor; Ferli Septi Irwansyah; Sharifuddin Bin Md Zain (Chemistry, 2023)
The demand for synthetic bone grafts has increased in recent years. Hydroxyapatite (HA) is one of the highly suitable candidates as a bone graft material due to its excellent biocompatibility and high osteoconductive properties with low toxicity. HA has disadvantageous mechanical strength showing relatively fragile and brittle behavior due to its high hygroscopic properties. This leads to improper mechanical properties for such grafting applications. Therefore, HA should be combined with another material with similar biocompatibility and high hardness, such as SiO2. In this work, HA/SiO2 (HAS) composite material was prepared via a hydrothermal method to obtain the high purities of HA with a particle size of approximately 35 nm and around 50% crystallinity. It was found that the addition of SiO2 stimulated the composite system by forming an orthosilicic acid complex that can reduce the overall solution’s pH, thus contributing to the integrity and stability of the HAS composite. Therefore, higher SiO2 contents in the HAS composite can enhance its mechanical stability when immersed in simulated body fluid (SBF). Our work demonstrated that HAS can highly improve HA material’s hardness and mechanical stability under immersion of SBF. The Vickers test showed that the 0.05 GPa hardness in 10% SiO2 increased to 0.35 GPa hardness with the addition of 20% SiO2. The crystal structures of HAS were analyzed using X-ray diffraction, and the morphology of the HAS composites was observed under electron microscopy.